(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The study aims to determine the effect of a teaching procedure of matching to sample (MTS) on the learning of monetary relations in deaf children with mathematic prerequisites and without them. Six deaf children Ensino de relações condicionais monetárias por meio de “Matching to Sample” para crianças surdas com e sem pré-requisitos matemáticos.Teaching conditional monetary relations through Matching to Sample to deaf children with and without mathematical prerequisites. Six deaf children were divided into two experimental groups (with and without mathematic prerequisites). They were taught via MTS about values in Brazilian Sign Language (LIBRAS) and their relations to: prices (AB), pictures of coins (AC) and facsimile of Brazilian Real bills (AD), followed by tests of symmetry and transitivity. Most participants showed emerging relations. Teaching via component-matching-training involved relations be-tween facsimile of Brazilian Real bills and prices (DB) and facsimile of Brazilian Real bills and pictures of coins (DC), followed by tests of symmetry, transitivity and generalization (simulation of buying and sell-ing). There was a difference in performance between the participants in Groups I and II, which confirm the importance of mathematic prerequisites to learn monetary relations.